Cutaneous myiasis in skin cancer and malignant wounds: a systematic review. (7th August 2021) - Cuestas, Daniel; Pedraza, John; Herrera, Hugo; Motta, Adriana; Cuestas, Andrés; Forero, Yency; Porras, Ricardo; Urrea, Fernando; Galvis, Dany; Galvis, Ingrid; Bernal, Maria‐Alejandra; Alvarado, Maria‐Victoria; et al.
Abstract: Background: Cutaneous myiasis in patients with malignant wounds or skin cancer is a rare and undesirable event with limited epidemiological data. A subregister of reports, lack of education in the population, inadequate empirical treatments, and medical underestimation are components of a public health problem that threatens patients' lives. Methods: We conducted a systematic review of the literature of cutaneous myiasis associated with malignant wounds and skin cancer, characterizing sociodemographic variables, risk factors, clinical and histological features, and treatment. Additionally, we present a demonstrative case with the adequate taxonomic evaluation. Discussion: Cutaneous myiasis is an underestimated and poorly managed infestation, which can generate severe complications in oncological patients. This is the first systematic review in the literature about this clinical scenario, which provides information to the physician and clinical researcher about the epidemiological gaps and what has been published so far. Conclusions: Findings from the current review have helped to display the sociodemographic, epidemiological, and clinical behavior of myiasis in skin cancer and malignant wounds. Its contribution to the greater tumor tissue destruction is clear; however, more studies are required. The therapeutic management in these patients is equally clarified.